2007
DOI: 10.1002/jcb.21472
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serum amyloid A transcripts in human bone tissues, differentiated osteoblast‐like stem cells and human osteosarcoma cell lines

Abstract: Although the liver is the primary site of cytokine-mediated expression of acute-phase serum amyloid A (SAA) protein, extrahepatic production has also been reported. Besides its role in amyloidosis and lipid homeostasis during the acute-phase, SAA has recently been assumed to contribute to bone and cartilage destruction. However, expression of SAA in human osteogenic tissue has not been studied. Therefore, we first show that SAA1 (coding for the major SAA isoform) but not SAA2 transcripts are expressed in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Interestingly, these inflammatory molecules are the ones responsible for both the hepatic and extrahepatic production of SAA (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these inflammatory molecules are the ones responsible for both the hepatic and extrahepatic production of SAA (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was performed using an RT-PCR kit according to the manufacturer's protocol (Invitrogen). DNase-treated RNA (1 lg) was used in the reverse transcription with random hexamers and oligo(dT) [12][13][14][15][16][17][18] as the extension primer. PCR was performed by denaturing at 94°C for 2 min, followed by incubation at 94°C for 15 s and 68°C for 1 min for 40 cycles.…”
Section: Isolation Of Rna and Rt-pcrmentioning
confidence: 99%
“…In our previous study, we demonstrated that the amount of circulating SAA is higher in the plasma of patients with osteosarcoma relative to that in the plasma of patients with benign osteochondroma (7). Studies have also shown that SAA is expressed in bone tissues and osteosarcoma cell lines (25) and that the amounts of SAA in the sera are associated with the relapse of osteosarcoma (26). These results further implicate the importance of this protein in the biology of osteosarcoma.…”
Section: Discussionmentioning
confidence: 60%